Go with the glow - Frank Berrios; Frank Berrios (Golden/Disney)
The fun doesn't end when the sun goes down with this Cars Reusable Glow-in-the-Dark Sticker book! Kids will love creating racing scenes and completing activities with more than 40 reusable stickers that glow in the dark!